Aortic Root Enlargement In Case of Double Valve Replacement (KYAMC Journal, 2020)
Rheumatic valvular heart disease is quite common in Bangladesh. It affects most commonly mitral and aortic valve. As a result of annular fibrosis, aortic root become smaller in some patients. So, if smaller prosthesis is implanted, there is gross patient prosthesis mismatch (PPM), poor LV regression, increase overload, and ultimately low survival rate. Its' to report our experience in aortic root enlargement in case of double valve replacement where a patient of severe mitral stenosis and aortic regurgitation with small aortic annulus requiring aortic root enlargement (ARE).Weaning from Cardiopulmonary bypass (CPB) was uneventful, perioperative and post operative period was satisfactory. Post-operative echocardiography revealed normally functioning prosthesis. In case of small aortic root, aortic root enlargement (ARE) can be safely done by double valve replacement to overcome the prosthetic patient mismatch (PPM).KYAMC Journal Vol. 11, No.-2, July 2020, Page 108-110